Thylakoid redox signals are integrated into organellar-gene-expression-dependent retrograde signaling in the prors1-1 mutant - Tadini, Luca; Romani, Isidora; Pribil, Mathias; Jahns, Peter; Leister, Dario; Pesaresi, Paolo (Frontiers in Plant Science, 2012)
Perturbations in organellar gene expression (OGE) and the thylakoid redox state (TRS) activate retrograde signalling pathways that adaptively modify nuclear gene expression (NGE), according to developmental and metabolic needs. The prors1-1 mutation in Arabidopsis down-regulates the expression of the nuclear gene Prolyl-tRNA Synthetase1 (PRORS1) which acts in both plastids and mitochondria, thereby impairing protein synthesis in both organelles and triggering OGE-dependent retrograde signalling. Because the mutation also affects thylakoid electron transport, TRS-dependent signals may likewise have an impact on the changes in NGE observed in this genotype. In this study, we have investigated whether signals related to TRS are actually integrated into the OGE-dependent retrograde signalling pathway. To this end, the chaos mutation (for chlorophyll a/b binding protein harvesting-organelle specific), which shows a partial loss of PSII antennae proteins and thus a reduction in PSII light absorption capability, was introduced into the prors1-1 mutant background. The resulting double mutant displayed a prors1-1-like reduction in plastid translation rate and a chaos-like decrease in PSII antenna size, whereas the hyper-reduction of the thylakoid electron transport chain, caused by the prors1-1 mutation, was alleviated, as determined by monitoring chlorophyll (Chl) fluorescence and thylakoid phosphorylation. Interestingly, a substantial fraction of the nucleus-encoded photosynthesis genes down-regulated in the prors1-1 mutant are expressed at nearly wild-type rates in prors1-1 chaos leaves, and this recovery is reflected in the steady-state levels of their protein products in the chloroplast. We therefore conclude that signals related to photosynthetic electron transport and TRS, and indirectly to carbohydrate metabolism and energy balance, are indeed fed into the OGE-dependent retrograde pathway to modulate NGE and adjust the abundance of chloroplast proteins.